Acute effects of various doses of nitrate-rich beetroot juice on high-intensity interval exercise responses in women: a randomized, double-blinded, placebo-controlled, crossover trial - Zhang Jiaqi; Dai Zihan; Stephen Heung-Sang Wong; Zheng Chen; Eric Tsz-Chun Poon (Taylor & Francis Group, 2024)
ABSTRACTBackground This study investigated the acute effects of various doses of nitrate-rich beetroot juice on the responses to high-intensity interval exercise in women.Methods A double-blinded, randomized, placebo-controlled, crossover trial was conducted with 13 recreationally active young women (age = 23 ± 2 years). All participants performed interval exercise (8 × 1-min bouts of cycling at 85% of peak power output [PPO] interspersed with 1-min active recovery at 20% of PPO) 2.5 h after consumption of the randomly assigned beetroot juice containing 0 mmol (placebo), 6.45 mmol (single-dose), or 12.9 mmol (double-dose) [Formula: see text]. The heart rate (HR), blood pressure, blood lactate, blood glucose, oxygen saturation, rating of perceived exertion (RPE), and emotional arousal were assessed.Results Nitrate supplementation significantly altered the HR and RPE responses across the three trials. The mean HR was lower in the single- and double-dose groups than in the placebo control group during both work intervals and recovery periods, as well as across the overall protocol (all p < .05). The mean RPE was lower in the single- and double-dose groups than in the control group during recovery periods and across the overall protocol (all p < .001). However, there was no significant difference in either HR or RPE between the single- and double-dose groups at any time point.Conclusions Acute nitrate ingestion led to significant decreases in the mean HR and RPE during high-intensity interval exercise, but no additional benefit was observed with higher nitrate content. These findings may assist practitioners in implementing more effective nitrate supplementation strategies during high-intensity interval exercise.